Developing teaching guidelines of learning numeracy through game card for preschool teachers / Nor Syazwani Mohd Rasid ... [et al.] - Mohd Rasid, Nor Syazwani; Md Nasir, Nurul Akmal; Singh, Parmjit; Cheong, Tau Han; Sueb, Rosilawati (Universiti Teknologi MARA, 2022)
In facing the challenges of Industry 5.0, the younger generation, in particular, needs to master the field of STEM. Hence, efforts in raising students' interest in STEM should include introducing numeracy skills earlier. However, providing appropriate pedagogy is crucial in developing numeracy skills among preschool children as this becomes the foundation for their future numeracy skills. Based on previous research, learning through play could increase children's interest, enjoyment, attention span, and confidence. Preschool teachers agreed that learning should incorporate games and activities. However, in the Malaysian setting, there are fewer specific guidelines, games, activities, or situations that maximise numeracy learning in the class designed crucially in a preschool setting. This study intends to develop teaching guidelines of learning numeracy through play for preschool teachers. This study utilised a mixed-methods design, called a sequential explanatory strategy. Fifty preschool teachers were selected using a stratified sampling technique to complete a questionnaire on their beliefs and attitudes toward learning through play. Six of them were interviewed concerning the bases needed to implement learning through play in the class. The result revealed that preschool teachers have a high positive level for both beliefs and attitudes toward learning mathematics through play. Then, based on the interview, teachers listed the bases needed before, during, and after implementing learning through play. This study produces teaching guidelines based on the Input-Process-Output model, which encompasses before, during, and after the teaching and learning process of numeracy through play.